PERLINDUNGAN LINGKUNGAN DALAM IKLIM INVESTASI UU CIPTAKERJA: PENGERUSTAMAAN ATAU PENGGERUSAN? - Ahamad Yulda Wildanu; Reza Fathi Husnullabib; M. Mun'am Syaiful Huda; Muhammad Battar Zakaria (Peneliti.net, 2023)
The Job Creation Law as the Omnibus Law has been enacted in Indonesia to encourage investment and accelerate economic development. One important aspect of the Job Creation Law is environmental protection, which is of concern to stakeholders, including civil society and environmental activists. In this analysis, it was found that the Job Creation Law provides for several environmental protection provisions, such as the obligation to carry out an environmental impact assessment (AMDAL) and an environmental management plan (RKL-RPL) for investment projects. However, there are concerns that this provision could be undermined, because the Job Creation Law provides several concessions that could reduce pre-existing standards of environmental protection. This can result in environmental degradation. This article also analyzes the potential risks of destroying the environment in the implementation of the Job Creation Law, such as weak oversight, limited public participation, and the potential for reduced access to the courts to involve civil society in decision-making processes related to the environment.